A CONCEPTUAL REVIEW OF DIGITAL CONTENT MARKETING STRATEGY AS AN EFFECTIVE PRACTICE TO GROW SMALL BUSINESS - Alzaanin, Rahma (FEB - Universitas Lampung, 2020)
We live in an era where everything is digitized. Nowadays, marketplace is showing an increasing number of online users and online applications due to technological inventions and rapid networks. Therefore, these advances is the driving force for the adoption of innovative business strategies. Free access and wide spread of digital platforms, social media and blogs encourage individuals to start small businesses. Accordingly, owners look for effective methods to reach out consumers and to market out their products or services which rise the possibility of business success and gradually lead to business growth. Digital marketing is the broad concept that includes various approaches, strategies and techniques. So that, this paper aims at discussing digital content marketing strategy as one of commonly used approach among small business by conducting a conceptual review that shad the lights on some theoretical researches and empirical studies of digital content. Keywords: digital content, business strategy, small business, business growth.